Impulsive buying pada perempuan dewasa awal: Bagaimana peranan self-control? - Muzammil, Indah Farchina Sari; Adnani Budi Utami; Karolin Rista (INNER: Journal of Psychological Research, 2023)
Abstract Early adulthood women should be able to suppress impulsive buying and be able to buy goods as needed. The fact is that there are still many early adult women who have not been able to control their impulsive buying behavior. This study aims to determine the relationship between self-control and impulsive buying in early adult women in Kemayoran Village, Bangkalan. The method used is a quantitative method. The research sample has the criteria of being a woman aged 25-40 years, has an online shopping application, and living in Kemayoran Village, Bangkalan. This research instrument uses an impulsive buying scale and a self-control scale. Data analysis using spearman rho. The results of data analysis show a significant value so the hypothesis in this study that there is a negative relationship between self-control and impulsive buying in early adult women is declared accepted. This means that there is a very significant negative relationship between self-control and impulsive buying. Based on the results of the data analysis, it can be concluded that the higher a person's self-control, the lower a person's impulsive buying behavior, and vice versa. Keywords: impulsive buying; self-control; Early Mature Women